Jivha Pariksha – An Ayurvedic Diagnostic tool: A Review - Sharma, Vandana; Yadav, Chhaju Ram; Sarika Yadav (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: The tongue is most convenient approach to observe changes in the body’s fundamental components and assess the progression of disease. The Ayurvedic Samhita lists several types of Rogi Pariksha that can be used to diagnose the disease. The Ashtavidha Pariksha, is described by Acharya Yogratnakar. Jivha Pariksha is one among them. Jivha Pariksha involves shape, colour, moisture, movement and the coating on the tongue. Jivha pariksha reveals our main constitution (normal prakruti), imbalance of dosha, state of agni (digestive fire) and koshtha (Annavaha strotas). According to Ayurveda Agnimandya (hypo functioning of digestive fire) is the root cause of all diseases. Saam jivha (Coated tongue) indicates a presence of Ama (undigested food) in the digestive system. Thick coating indicates the progression of disease so Jivha Pariksha is very important in diagnosis as well as prognosis of various diseases. Aim – To Study the significance of Jivha Pariksha in diagnostic tools. Objectives – To Study importance of Jivha Pariksha in diagnostic methodology from Ayurveda texts and its application in diagnosing the various kind of diseases. Material and methods – This is a conceptual study for which various Ayurveda and modern text, Samhitas, published articles, research papers and information available on internet is used. Discussion – Jivha pariksha is very important in routine examination of patient as it is a part of Ashtvidha Pariksha. During examination one should have knowledge about the shape, colour, coat of the tongue. For appropriate disease diagnosis and treatment, a proficient understanding of Jivha parikhsha is required. Result – Jivha pariksha is very important tool in Ayurveda for the diagnosis and prognosis of disease. The jiva pariksha is a significant diagnostic and prognostic tool in the medical field.